Determination method for magnetic momentum compensation temperature of ferrimagnets by extrapolating from narrow temperature range - Chang, Jun-Young; Jeong, Yun-Chae; Lee, Ah-Yeon; Choi, Yeon Suk; Park, Seung-Young; Min, Byoung Chul; Je, Soong-Geun; Choe, Sug-Bong; Kim, Duck Ho (American Institute of Physics, 2024)
We propose here an experimental method to determine the magnetization compensation temperature of ferrimagnets. Our method utilizes the first-order derivative of the spontaneous net magnetization with respect to the temperature and then analyzes the results within the context of the Bloch's law of ferrimagnetic materials. This method enables us to extrapolate the compensation temperatures, even when they exceed the measurement limit. Consequently, a wide range of compensation temperatures can be determined using a single experimental setup. The present method provides a versatile tool for analyzing huge compensation temperature in the emerging field of ferrimagnetic and antiferromagnetic spintronics.